Smart Biomedical and Physiological Sensor Technology XVI 2019
DOI: 10.1117/12.2524503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coil size on transcranial magnetic stimulation (TMS) focality

Abstract: In recent years, there is an increasing interest in noninvasive treatments for neurological disorders like Alzheimer and Depression. Transcranial magnetic stimulation (TMS) is one of the most effective methods used for this purpose. The performance of TMS highly depends on the coils used for the generation of magnetic field and induced electric field particularly their designs affecting depth and focality tradeoff characteristics. Among a variety of proposed and used TMS coil designs, circular coils are common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Various TMS coil geometries have been adopted along with additional methods for field divergence improvement [19][20][21][22][23][24][25]. To optimize the TMS coil's electric field distribution, theoretical analysis based on analytical models [26][27][28][29] or numerical simulations using either finite element method (FEM) or finite difference method [30][31][32][33][34][35][36][37] have been implemented along with additional physical and experimental verifications [38][39][40] and rodent experiments [41][42][43]. The coil performance is generally governed by a depth¬-spread tradeoff [25].…”
Section: Introductionmentioning
confidence: 99%
“…Various TMS coil geometries have been adopted along with additional methods for field divergence improvement [19][20][21][22][23][24][25]. To optimize the TMS coil's electric field distribution, theoretical analysis based on analytical models [26][27][28][29] or numerical simulations using either finite element method (FEM) or finite difference method [30][31][32][33][34][35][36][37] have been implemented along with additional physical and experimental verifications [38][39][40] and rodent experiments [41][42][43]. The coil performance is generally governed by a depth¬-spread tradeoff [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous works have been focused on introducing new coils with improved depth-focality performance and reduced spot size. These were done through analytical models or numerical simulations using either the finite element method (FEM) or finite difference method (FDM) [15,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported the designs of rodent-specific TMS coils [ 23 , 27 , 28 ]. In general, these coils either stimulate a large portion of the rodent brain or the induced field is too weak to reach suprathreshold brain stimulation, as Bagherzadeh and Choa [ 21 ] pointed out. High permeability materials can enhance magnetic field strength and have been applied to design TMS coils for humans [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of TMS coil geometries have been adopted along with additional methods for field divergence improvement [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . To optimize the design of TMS coil's electric field distribution, theoretical analysis based on analytical models 12,[29][30][31][32] or numerical simulations using either finite element method (FEM) or finite difference method (FDM) [33][34][35][36][37][38][39][40][41][42] have been implemented along with additional physical and experimental verifications [43][44][45] . In general, the coil performance is governed by a depth-spread tradeoff 27 .…”
Section: Introductionmentioning
confidence: 99%